The repeatability of behavioural laterality during nest building in zebra finches - Andrés Camacho-Alpízar; Jessica Hewitt; Cailyn Poole; Tristan Eckersley; Benjamin A. Whittaker; Julia L. Self; Lauren M. Guillette (Animal Cognition)
Abstract Cerebral laterality is a widespread phenomenon across animals and refers to the specialization of the left and right hemispheres of the brain for perceptual, cognitive and behavioural tasks. Behavioural laterality occurs in several contexts, including foraging, mate selection, predator detection and tool manufacture. Behavioural laterality during nest building, however, has rarely been addressed. We conducted two experiments to examine (1) whether behavioural laterality occurs during nest building, (2) whether laterality correlates with nest-building speed, (3) whether laterality during nest building is repeatable, and (4) whether nest-building experience influences laterality. In Experiment 1, we scored individual laterality indices for 58 zebra finch (Taeniopygia guttata) males, the nest-building sex in this species, based on which eye he used to view then select the first 25 pieces of nest material. We calculated correlations between laterality strength and nest-building duration. In Experiment 2, to test the repeatability of laterality during nest building, we measured laterality for 20 males across five nests built by each male. Individuals varied both in the direction and the strength of behavioural laterality of material selection during nest building. Overall, however, males were not consistent in their laterality across the five nests. We found no correlation between laterality strength and nest-building duration in either experiment. Finally, we found evidence for building experience influencing the behavioural laterality of individuals: more building experience results in more predictable behavioural laterality during nest-material selection.